2013
DOI: 10.1155/2013/324234
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Level Laser in Chronic Tinnitus Treatment

Abstract: The purpose of this study was to evaluate the effect of medium-level laser therapy in chronic tinnitus treatment. In a prospective double-blind placebo-controlled trial, either active laser (450 mW, 830 nm combined Ga-Al-As diode laser) or placebo irradiation was applied through the external acoustic meatus of the affected ear towards the cochlea. Fourty-eight patients with chronic tinnitus were studied. The main outcome was measured using the Goebel tinnitus questionnaire, visual analogue scales measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In this study, participants who had improvements in perceived duration of tinnitus or tinnitus loudness matches two weeks after LLLT, had significantly worse pure-tone thresholds compared to participants who showed no improvement (Table 4). Previously, Dejakum et al 20 applied medium-level (450 mW) laser therapy with the same wavelength (830 nm) to our study for chronic tinnitus 20 , but there was no therapeutic effect Treatment outcomes of tinnitus were compared between baseline and two weeks after 10-interventions. Respondents were defined as participants who improved the duration of tinnitus by at least one point or improved the tinnitus loudness matches by more than 5 dB SL.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, participants who had improvements in perceived duration of tinnitus or tinnitus loudness matches two weeks after LLLT, had significantly worse pure-tone thresholds compared to participants who showed no improvement (Table 4). Previously, Dejakum et al 20 applied medium-level (450 mW) laser therapy with the same wavelength (830 nm) to our study for chronic tinnitus 20 , but there was no therapeutic effect Treatment outcomes of tinnitus were compared between baseline and two weeks after 10-interventions. Respondents were defined as participants who improved the duration of tinnitus by at least one point or improved the tinnitus loudness matches by more than 5 dB SL.…”
Section: Discussionmentioning
confidence: 97%
“…A 450 mW infrared laser, which is more than 10 times stronger than our setup, has been used as a therapeutic alternative in chronic tinnitus with no patient discomfort. 31 Furthermore, in the hidden cochlear implant concept, the implanted unit would be able to communicate with the hidden external unit through the Bluetooth low energy module and give feedback about the signal strength and any possible misalignments during initial calibration. This could decrease energy consumption by reducing any unnecessary light intensity and minimising tissue heating.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind, placebo-controlled trial from Austria, 48 patients showed no significant therapeutic effect in comparison to placebo [87]. …”
Section: Neuromodulation – Instrument-based Medical Interventionsmentioning
confidence: 99%